Photocatalytic remediation of persistent organic pollutants (POPs): A review - Van-Huy Nguyen; Siwaporn Meejoo Smith; Kitirote Wantala; Puangrat Kajitvichyanukul (Arabian Journal of Chemistry, 2020)
The release of persistent organic pollutants (POPs) into the environment is an issue of global concern, as the chemicals are stable over a prolonged period resulting in their accumulation in many animals and plants. Although POPs are banned in several countries, many chemicals have been proposed as POP candidates to be added to the existing compounds as defined by the United Nations Stockholm Convention committee. To address the safe disposal and clean-up of such chemicals, new, and especially cost-effective, remediation technologies for POPs are urgently required. This review focuses on existing POPs and the types of remediation processes available for their removal. Particular attention is paid towards photocatalysis using nanocatalysts in this review, due to their effectiveness towards POP degradation, technological feasibility, and energy and cost-efficiency. The underlying principles and the key mechanisms of the photocatalysts based on TiO2 based materials, metal oxides, light-assisted Fenton systems, framework materials e.g. metal-organic frameworks and polyoxometalates, including metal-free and hybrid photocatalysts for POPs cleanup are described for advance applications in solving the POPs contamination in the environment. The improvements of photocatalytic performance especially the POPs removal mechanism using the conventional and modified process, the design and optimization of photoreactors, and the integration technology are the critical challenges for the emerging pollutants and require intensive research for the forthcoming future.